Hypsizygus marmoreus as a Source of Indole Compounds and Other Bioactive Substances with Health-Promoting Activities - Katarzyna Kała; Wojciech Pająk; Katarzyna Sułkowska-Ziaja; Agata Krakowska; Jan Lazur; Maciej Fidurski; Krystian Marzec; Piotr Zięba; Agata Fijałkowska; Agnieszka Szewczyk; Bożena Muszyńska (Molecules, 2022)
Hypsizygus marmoreus is an edible medicinal mushroom species with a high dietary value. In this study, the fruiting bodies of commercial and self-cultivated crops and mycelium from in vitro H. marmoreus cultures (both white and brown varieties) were evaluated. This study aimed to analyze the presence of indole compounds and other biologically active substances and determine the effect that the addition of zinc and magnesium ions to the culture medium has on the content of the tested compounds in mycelial cultures. The content of indole compounds and other organic compounds was determined using high-performance liquid chromatography, the content of bioelements was determined using flame atomic absorption spectrometry, the glucan content was determined spectrophotometrically, and the antioxidant activity of extracts was estimated using DPPH, FRAP, and ABTS methods. The results showed that H. marmoreus mycelium from in vitro cultures is a good source of indole compounds, bioelements, glucans, and lovastatin. Mycelia from in vitro cultures showed the most diverse composition of indole compounds (L-tryptophan, 5-hydroxy-L-tryptophan, tryptamine, 5-methyltryptamine, and melatonin). Additionally, in vitro cultures of H. marmoreus enriched with Zn and Mg salts increased the contents of Na, Ca, Zn, 5-methyltryptamine, melatonin, protocatechuic acid, sterols, and total glucans. Only in the case of the white variety of mycelial enriched cultures, ergothioneine and Mg levels also increased. To summarize, the content of the active compounds differed depending on the H. marmoreus variety and the tested material.